2012
DOI: 10.1002/ep.11612
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of some of the parameters involved in inclined solar distillation systems

Abstract: There are two main problems of inclined solar water distillation systems. There is not a water film layer enough to facilitate the evaporation of water on the absorber plate, and high temperature of glass cover decreases the amount of condensed water. In this article, an inclined solar water distillation system was designed and tested under actual environmental conditions of Turkey in order to overcome these two main problems. Therefore, with this study, improving of inclined solar water distillation system pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 17 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Over the past century, nearly hundreds of solar still plants and thousands of individual stills have been built around the world [12][13][14]. The sun's energy heats water to the point of evaporation.…”
Section: Solar Distillationmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past century, nearly hundreds of solar still plants and thousands of individual stills have been built around the world [12][13][14]. The sun's energy heats water to the point of evaporation.…”
Section: Solar Distillationmentioning
confidence: 99%
“…This process removes impurities such as salts and heavy metals as well as eliminates microbiological organisms. Over the past century, nearly hundreds of solar still plants and thousands of individual stills have been built around the world [12][13][14].…”
Section: Solar Distillationmentioning
confidence: 99%
“…A higher temperature difference between these surfaces yields higher productivity. To maintain this temperature difference, various methods were proposed [47].…”
Section: The Basic Components Of a Solar Still Are Briefly Described mentioning
confidence: 99%
“…External reflector plates [17] at different inclination angles were used to increase the radiation incidence on the solar still. Deniz [18] investigated the effect of parameters such as gap distance, slope of cover and cooling of the cover on the performance of the still. Anburaj et al [19] demonstrated an optimum 30°inclination for an inclined solar still with rectangular grooves which yielded 3.77 L/day fresh water.…”
Section: Introductionmentioning
confidence: 99%